Ethionamide Population Pharmacokinetic Model and Target Attainment in Multidrug-Resistant Tuberculosis - Al-Shaer, Mohammad H; Märtson, Anne-Grete; Alghamdi, Wael A; Alsultan, Abdullah; An, Guohua; Ahmed, Shahriar; Alkabab, Yosra; Banu, Sayera; Houpt, Eric R; Ashkin, David; Griffith, David E; Cegielski, J Peter; et al. (Antimicrobial agents and chemotherapy, 2020)
Ethionamide (ETA), an isonicotinic acid derivative, is part of the multidrug-resistant tuberculosis (MDR-TB) regimen. The current guidelines have deprioritized ETA because it is potentially less effective than other agents. Our aim was to develop a population pharmacokinetic (PK) model and simulate ETA dosing regimens in order to assess target attainment. This study included subjects from four different sites, including healthy volunteers and patients with MDR-TB. The TB centers included were two in the United States and one in Bangladesh. Patients who received ETA and had at least one drug concentration reported were included. The population PK model was developed, regimens with a total of 1,000 to 2,250 mg daily were simulated, and target attainment using published MICs and targets of 1.0-log kill and resistance suppression was assessed with the Pmetrics R package. We included 1,167 ethionamide concentrations from 94 subjects. The final population model was a one-compartment model with first-order elimination and absorption with a lag time. The mean (standard deviation [SD]) final population parameter estimates were as follows: absorption rate constant, 1.02 (1.11) h ; elimination rate constant, 0.69 (0.46) h ; volume of distribution, 104.16 (59.87) liters; lag time, 0.43 (0.32) h. A total daily dose of 1,500 mg or more was needed for ≥90% attainment of the 1.0-log kill target at a MIC of 1 mg/liter, and 2,250 mg/day led to 80% attainment of the resistance suppression target at a MIC of 0.5 mg/liter. In conclusion, we developed a population PK model and assessed target attainment for different ETA regimens. Patients may not be able to tolerate the doses needed to achieve the predefined targets supporting the current recommendations for ETA deprioritization.